Governança corporativa e a distribuição de dividendos no setor bancário brasileiro - Paiva, José Fernando Martins de (2016)
The distribution of the company\'s profits is an important topic to be considered by investors in the allocation of its financial resources. This source of funds is also important for the company, since the profits of retention can finance new projects for their growth. There is no consensus on the payment of dividends, especially by regulatory peculiarities involving this issue in Brazil. The financial sector is often excluded from the samples by financial and accounting characteristics of this sector, despite significant as developers of popular economy and source of funding for companies. This research intended to relate the distribution of dividends and interest on capital of financial institutions with the highest levels of Corporate Governance of BM&FBOVESPA. The allocation of investor´s resources objectively to maximize their profits with little risk as possible, and at that point, the Corporate Governance provides mechanisms that would contribute in this direction. Using only public data available, all the informations were collected in the Central Bank of Brazil website, the CVM website and in the website of banks. With a sample of 98 companies totaling 702 observations for the period 2002-2014, and by linear regression by Stepwise adaptive method, the results indicated a positive association between the distribution of dividends, here represented by the dependent variable Earnings and the highest Levels of Corporate Governance. Also appointed a negative relationship between the same dependent variable and government control of financial institutions, and significant results with ROE variables, Debts, TJLP and LogATIVO, however, as well as the relationship with the mechanisms of Corporate Governance, was expected more consistent results to the macroeconomic factors.